Large‐Scale Modification of Commercial Copper Foil with Lithiophilic Metal Layer for Li Metal Battery. Issue 5 (14th January 2020) - Cui, Shiqiang; Zhai, Pengbo; Yang, Weiwei; Wei, Yi; Xiao, Jing; Deng, Libo; Gong, Yongji
Abstract: The application and development of lithium metal battery are severely restricted by the uncontrolled growth of lithium dendrite and poor cycle stability. Uniform lithium deposition is the core to solve these problems, but it is difficult to be achieved on commercial Cu collectors. In this work, a simple and commercially viable strategy is utilized for large‐scale preparation of a modified planar Cu collector with lithiophilic Ag nanoparticles by a simple substitution reaction. As a result, the Li metal shows a cobblestone‐like morphology with similar size and uniform distribution rather than Li dendrites. Interestingly, a high‐quality solid electrolyte interphase layer in egg shell‐like morphology with fast ion diffusion channels is formed on the interface of the collector, exhibiting good stability with long‐term cycles. Moreover, at the current density of 1 mA cm −2 for 1 mAh cm −2, the Ag modified planar Cu collector shows an ultralow nucleation overpotential (close to 0 mV) and a stable coulombic efficiency of 98.54% for more than 600 cycles as well as long lifespan beyond 900 h in a Li|Cu‐Ag@Li cell, indicating the ability of this method to realize stable Li metal batteries. Finally, full cells paired with LiNi0.8 Co0.1 Mn0.1 O2 show superior rate performance and stability compared with those paired with Li foil. Abstract : It is of great value to deposit lithium on copper foil uniformly without the presence of lithium dendrite. Through a simple displacement reaction, the copper foil is modified by uniform silver nanoparticles. Because of the presence of the lithiophilic Ag, the plating lithium metal exhibits pebble‐like morphology on the current collector, which helps to show good cycle stability in practical application.